Análise das transformações recentes na atividade agrícola da região sudoeste de Goiás: 1970/1995-6 - Ferreira, Débora Ferguson (2001)
The proposal of this síudy is to anlyse the transformation occurred in the agriculture of Southwest of Goiás. In order to achieve this target, the following microregions were selected: Meia Ponte, Southwest of Goiás and Rio dos Bois Valley, all present in the agricultural census of IBGE Foundation, based on the years of 1970,1975, 1980, 1985 and 1995/96. The analysis was done through the following procedure: statistical data collection in order to establish the evolution of Brazilian agriculture in the period from 1970 to 1995/96; the reading of texts by authors in Economics, to understand the technological changes which aífect the rural area; interviews were carried out with farmers, agronomists, owners of agricultural products dealers and bank managers. The study was developed, fírstly, by approaching the theoretical aspects which deal with modemization in agriculture. Following this, the process of modemization of Brazilian agriculture is reported, after that, the encouragement policies for agriculture in Brazilian “cerrados” are presented and, fínally, the transformation occurred in the agriculture of the Southwest of Goiás is studied. Through the results it was possible to perceive, in the region, the results it was possible to perceive, in the region, the substitution of cultures of lower intrinsic value by the ones of higher intrinsic value. It was also noticed that there was growth in the productivity of all produce analyzed, drie to the use of new technologies and that the rural credit (loans) was the main determinant in the initial process of modemization of agriculture in the region of Southwest of Goiás.